A porous carbon supported ir doped pt-based alloy catalyst and a preparation method thereof
Patent Information
- Application Number
- CN202310798617.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-06-30
AI Technical Summary
[0004]本发明的目的在于克服上述现有技术的缺点,提供一种多孔碳负载Ir掺杂Pt基合金催化剂及其制备方法,以解决现有技术中Pt颗粒作为催化剂材料成本高昂,适用性窄,稳定性不高的问题
[0020]本发明公开了一种多孔碳负载Ir掺杂Pt基合金催化剂的制备方法,属于催化剂材料制备领域。该制备方法首先合成多孔碳负载Pt基合金催化剂材料,多孔碳表面被Pt和过渡金属M的合金包覆,然后,通过酸刻蚀合金表面的非Pt过渡金属元素,在合金表面创造Ir的附着位点,最后,加入醋酸铱,通过高温油浴法,使Ir在合金表面形核,最终得到的材料为一种碳负载型Ir掺杂Pt基合金催化剂。该方法在合金化的同时,对整个催化剂的表面结构组成进行控制,进一步抑制廉价过渡金属溶解,改善催化活性和稳定性。本发明可以实现不同组分合金催化剂的合成,Ir的掺杂能够大幅度提高合金表面贵金属原子的暴露,还能够有效阻止廉价过渡金属溶解,从而显著提高合金催化剂的活性和稳定性。
Smart Images

Figure CN117117210B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalytic materials technology, specifically relating to a porous carbon-supported Ir-doped Pt-based alloy catalyst and its preparation method. Background Technology
[0002] Energy is the material foundation for human survival and the driving force for social progress. However, the energy structure dominated by non-renewable fossil fuels such as coal, oil, and natural gas has led to a series of environmental problems. Developing clean and efficient new energy technologies, such as fuel cells and water electrolysis, is now urgently needed.
[0003] Pt particles supported on high specific surface area carbon are the preferred catalyst material for these new energy technologies. However, during the catalytic process, CO is adsorbed onto the Pt surface through strong π bonds, leading to its poisoning and deactivation. Furthermore, Pt is a precious metal, scarce in reserves and expensive, meaning large-scale use would inevitably require very high raw material costs. Therefore, for these new energy technologies, designing and developing catalysts that are low-cost, highly active, and stable is of paramount importance. Summary of the Invention
[0004] The purpose of this invention is to overcome the shortcomings of the prior art and provide a porous carbon-supported Ir-doped Pt-based alloy catalyst and its preparation method, so as to solve the problems of high cost, narrow applicability and low stability of Pt particles as catalyst materials in the prior art.
[0005] To achieve the above objectives, the present invention employs the following technical solution:
[0006] A method for preparing a porous carbon-supported Ir-doped Pt-based alloy catalyst includes the following steps:
[0007] Step 1: Porous carbon, platinum metal salt, and other metal salts are added to oleylamine to obtain a mixed system. After ultrasonic treatment of the mixed system, hexadecyltrimethylammonium bromide is added, and the mixture is treated in a sealed oil bath. After the oil bath treatment, the reaction product is centrifuged, washed, and dried to obtain a porous carbon-supported Pt-based alloy material. The other metal salts are metal salts corresponding to transition metals other than platinum metal salt and iridium metal salt.
[0008] Step 2: Dissolve the porous carbon-supported Pt-based alloy material in ethylene glycol, add hydrochloric acid and stir, then add iridium acetate to form a reaction system; after the reaction system is treated in an oil bath, the reaction product is centrifuged, washed, and dried to obtain the porous carbon-supported Ir-doped Pt-based alloy catalyst.
[0009] A further improvement of the present invention is that:
[0010] Preferably, in step 1, the mixing ratio of porous carbon to oleylamine is (10-20 mg): 30 mL; the mixing ratio of metal salt to oleylamine is (5-15 mg): 15 mL.
[0011] Preferably, in step 1, the total amount of platinum metal salt and other metal salts added is ≤30mg.
[0012] Preferably, in step 1, the amount of hexadecyltrimethylammonium bromide added is 2-4 times the total amount of metal salt added.
[0013] Preferably, in step 1, the oil bath time is 30-180 min and the oil bath temperature is 170-230℃.
[0014] Preferably, in step 2, the mixing ratio of porous carbon-supported Pt-based alloy material to ethylene glycol is (10-30 mg): 30 mL.
[0015] Preferably, in step 2, the ratio of added hydrochloric acid to porous carbon-supported Pt-based alloy material is 5 μL: 1 mg.
[0016] Preferably, in step 2, the amount of iridium acetate added is 0.1-0.5 times the amount of porous carbon-supported Pt-based alloy material added.
[0017] Preferably, in step 2, the oil bath time is 10-30 minutes and the oil bath temperature is 120-165℃.
[0018] A porous carbon-supported Ir-doped Pt-based alloy catalyst prepared by any of the above preparation methods, wherein the porous carbon surface is coated with alloy nanoparticles, the alloy nanoparticles being an alloy composed of Ir, Pt and metal M, wherein metal M is a transition metal other than Ir and Pt.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] This invention discloses a method for preparing a porous carbon-supported Ir-doped Pt-based alloy catalyst, belonging to the field of catalyst material preparation. The method first synthesizes a porous carbon-supported Pt-based alloy catalyst material. The porous carbon surface is coated with an alloy of Pt and a transition metal M. Then, non-Pt transition metal elements on the alloy surface are etched with acid to create Ir attachment sites. Finally, iridium acetate is added, and Ir nucleates on the alloy surface using a high-temperature oil bath method. The resulting material is a carbon-supported Ir-doped Pt-based alloy catalyst. This method controls the surface structure composition of the entire catalyst while alloying, further inhibiting the dissolution of inexpensive transition metals and improving catalytic activity and stability. This invention can achieve the synthesis of alloy catalysts with different compositions. Ir doping can significantly increase the exposure of noble metal atoms on the alloy surface and effectively prevent the dissolution of inexpensive transition metals, thereby significantly improving the activity and stability of the alloy catalyst.
[0021] This invention also discloses a porous carbon-supported Ir-doped Pt-based alloy catalyst. The catalyst uses porous carbon as a support internally, with the surface of the porous carbon coated with alloy nanoparticles. These alloy nanoparticles are composed of Ir, Pt, and metallic M. The introduced transition metal can modify the electronic structure of Pt through ligand and stress effects, enhancing its resistance to CO poisoning. Furthermore, most transition metals are inexpensive, and appropriate doping can reduce the amount of Pt used without affecting catalytic activity, thus lowering catalyst costs. By replacing M on the alloy surface with Ir doping, the Pt alloy can inhibit alloy dissolution, significantly improving the stability of the alloy catalyst and the utilization rate of noble metal atoms. The porous carbon has good electrical conductivity, which facilitates electron transport during catalysis, and its large specific surface area ensures uniform dispersion of the alloy particles, thereby significantly reducing catalyst costs and improving its catalytic activity, demonstrating high practical value.
[0022] Furthermore, in this catalyst, porous carbon serves as the conductive support for the alloy catalyst. The alloy surface is composed of Ir and Pt elements, while the interior of the alloy is composed of Pt and M. Because M can be any alloy, the catalyst can adjust its alloy type according to different application fields. This alloy surface structure composed of noble metals significantly increases the exposure of noble metal atoms, thereby improving the catalytic activity of the catalyst. Since Ir and Pt are stable in acidic and alkaline catalytic environments, the catalyst can be used for a long time during operation, thus significantly improving its stability.
[0023] Furthermore, the metal M can be a monometallic metal or a multi-element alloy, and its type and quantity can be adjusted according to the application field and requirements of the catalyst, making the porous carbon-supported Ir-doped Pt-based alloy catalyst applicable to a wide range of applications. Attached Figure Description
[0024] Figure 1The XRD pattern of the product shown in Example 1;
[0025] Figure 2 The SEM and EDS images of the product morphology shown in Example 1 are shown below.
[0026] In this figure, (a) is a SEM image; and (b) is an EDS image.
[0027] Figure 3 The TEM image is of the product shown in Example 1. Detailed Implementation
[0028] The present invention will be further described in detail below with reference to specific embodiments:
[0029] One embodiment of the present invention discloses a porous carbon-supported Ir-doped Pt-based alloy catalyst. The catalyst has the structure of a porous carbon-supported Ir-doped Pt-based alloy catalyst. Specifically, the porous carbon surface is coated with alloy nanoparticles composed of Ir, Pt and metal M. The porous carbon is hollow XC-72 carbon, which has pores inside and is not a hollow structure. The metal M is a transition metal other than Ir and Pt.
[0030] Preferably, the metal M is a monometallic metal or a multi-element alloy.
[0031] One embodiment of the present invention discloses a method for preparing a porous carbon-supported Ir-doped Pt-based alloy catalyst, comprising the following steps:
[0032] (1) Weigh an appropriate amount of porous carbon and metal salt and dissolve them in oleylamine. After sonication for a period of time, add an appropriate amount of hexadecyltrimethylammonium bromide (CTAB) and perform a sealed oil bath. After the oil bath, perform centrifugal washing and then drying to obtain a porous carbon-supported Pt-based alloy material. The metal salt includes platinum metal salt and other transition metal M corresponding metal salts. The other transition metal salts are metal salts other than platinum metal salts and iridium metal salts. Preferably, the platinum metal salt can be platinum acetylacetonate, and the transition metal salt can be copper acetylacetonate and nickel acetylacetonate. Acetylacetonate-type metal salts are more likely to release Pt ions and M ions, so as to form an alloy in the future.
[0033] Specifically, the mixing ratio of porous carbon to oleylamine is (10-20 mg): 30 mL; the mixing ratio of metal salt to oleylamine is (5-15 mg): 15 mL, and the total amount of metal salt added is ≤30 mg. The limitation on the total amount of metal salt added serves two purposes: firstly, to ensure uniform dispersion on the surface of the porous carbon, avoiding agglomeration due to excessive addition; and secondly, to ensure high dispersion in the oleylamine solution, facilitating nucleation and growth into nanoparticles.
[0034] Specifically, the amount of hexadecyltrimethylammonium bromide (CTAB) added is 2-4 times the total amount of metal salts, including Pt, added.
[0035] Specifically, the oil bath time is 30-180 minutes, and the oil bath temperature is 170-230℃.
[0036] In this process, the metal salt first forms a metal cation solution in an oleylamine solution, and then is reduced to individual metal nuclei under the action of an oil bath and hexadecyltrimethylammonium bromide (CTAB). Different metal nuclei are adsorbed on the porous carbon surface and form an alloy structure through interdiffusion, resulting in a porous carbon-supported Pt-based alloy material, PtM. Essentially, the carbon pores on the porous carbon surface are defects with high surface energy, which is more conducive to the nucleation and stability of metal ions, making it easier for alloy particles to form at the carbon pore sites on the surface.
[0037] (2) Weigh an appropriate amount of the porous carbon-supported Pt-based alloy material obtained in step (1) and dissolve it in ethylene glycol to form a carbon-supported Pt-based alloy / ethylene glycol solution. Add an appropriate amount of hydrochloric acid and seal and stir for a period of time. Then add a certain amount of iridium acetate to form a reaction system. After the reaction system is in an oil bath for a period of time, the reaction product solution is obtained. The reaction product solution is centrifuged, washed, and dried to obtain a porous carbon-supported Ir-doped Pt-based alloy catalyst.
[0038] Specifically, the mixing ratio of porous carbon-supported Pt-based alloy material to ethylene glycol is (10-30 mg): 30 mL.
[0039] Specifically, the concentration of hydrochloric acid used was 6 mol / L, and the ratio between its addition and the porous carbon-supported Pt-based alloy material was 5 μL: 1 mg.
[0040] Specifically, the amount of iridium acetate added is 0.1-0.5 times that of the porous carbon-supported Pt-based alloy material.
[0041] Specifically, the oil bath time is 10-30 minutes, and the oil bath temperature is 120-165℃.
[0042] In this process, the composite alloy particles PtM on the porous carbon surface are etched with hydrochloric acid. The acidic environment is a strong oxidizing environment, and the transition metal has a lower oxidation potential than Pt, making it more susceptible to oxidation and corrosion in the acidic solution. This causes compounds to dissolve into the solution, resulting in the dissolution of the transition metal on the Pt-M alloy surface under acidic conditions. This leads to the loss of surface atoms, providing space for the subsequent introduction of Ir. The entire acid etching process extends from the alloy surface inwards. By controlling the etching time, only the M metal on the PtM surface is etched, and then Ir is introduced onto the surface, thus achieving a composite alloy structure with PtM inside and PtIr on the surface.
[0043] In the above preparation process, the metal salt first forms a metal cation solution in an oleylamine solution, and then is reduced to a metal nucleus under the action of an oil bath and hexadecyltrimethylammonium bromide (CTAB). The metal nucleus is adsorbed on the porous carbon surface and forms an alloy structure through interdiffusion, resulting in a porous carbon-supported Pt-based alloy material. Hydrochloric acid can etch the M element on the surface of the porous carbon-supported Pt-based alloy. After adding iridium acetate, under the reduction action of ethylene glycol, the Ir metal nucleus is adsorbed at the etched sites on the alloy surface, forming a porous carbon-supported Ir-doped Pt-based alloy catalyst. This method is novel, simple, and has broad application prospects.
[0044] Example 1
[0045] 15 mg of XC-72 carbon was dissolved in 30 ml of oleylamine and stirred continuously. Then, 10 mg of platinum acetylacetonate, 5 mg of copper acetylacetonate, and 5 mg of nickel acetylacetonate were added sequentially. After sonication for 30 min, 60 mg of cetyltrimethylammonium bromide (CTAB) was added. The mixture was sealed and incubated in an oil bath at 200 °C to form a porous carbon-supported Pt-based alloy material / oleylamine mixed solution. After reacting for 40 min, the solution was allowed to cool naturally. The mixture was centrifuged at 10000 r / min to collect the precipitate, which was then washed repeatedly with ethanol for 20 min each time, for a total of 3 centrifugation washes. Finally, the precipitate was placed in a vacuum oven at 60 °C for 12 h, ground into powder, and set aside for later use.
[0046] 20 mg of the prepared porous carbon-supported Pt-based alloy material was weighed and dissolved in 30 mL of ethylene glycol. 100 μL of 6 mol / L hydrochloric acid was added, and the mixture was stirred for 15 min. Then, 5 mg of iridium acetate was added, and the mixture was sealed. The mixture was then placed in an oil bath at 130 °C for 20 min. After the reaction was completed, the mixture was allowed to cool naturally and centrifuged at 8000 r / min for 30 min. The mixture was washed three times with a 1:1 mixture of ethanol and deionized water. After centrifugation, the precipitate was placed in a vacuum oven at 60 °C and dried for 12 h to obtain the porous carbon-supported Ir-doped PtNiCu alloy catalyst.
[0047] Figure 1 The XRD pattern of the porous carbon-supported Ir-doped PtNiCu alloy catalyst obtained in Example 1 of this invention shows that the material prepared in Example 1 exhibits typical multi-element alloy properties with its XRD characteristic peaks falling between the characteristic peaks of Pt (JCPDS No. 04-0802), Ir (JCPDS No. 06-0598), Ni (JCPDS No. 04-0850), and Cu (JCPDS No. 04-0836).
[0048] Figure 2The SEM and EDS spectra of the porous carbon-supported Ir-doped PtNiCu alloy catalyst obtained in Example 1 of this invention are shown in Figure (a) as an SEM image and Figure (b) as an EDS image. It can be seen from the figures that the prepared porous carbon-supported Ir-doped PtNiCu alloy catalyst has uniform size. Table 1 shows the elements and their contents in the EDS images. It can be seen from the table that Pt, Ir, Ni and Cu elements are present.
[0049] Table 1. Elemental content of porous carbon-supported Ir-doped PtNiCu alloy catalyst prepared in Example 1
[0050]
[0051]
[0052] Figure 3 The TEM image of the porous carbon-supported Ir-doped PtNiCu alloy catalyst obtained in Example 1 of the present invention shows that the prepared porous carbon-supported Ir-doped PtNiCu alloy catalyst is a structure in which the porous carbon surface is wrapped by Ir-doped PtNiCu alloy.
[0053] Example 2
[0054] 10 mg of XC-72 carbon was dissolved in 30 ml of oleylamine and stirred continuously. Then, 8 mg of platinum acetylacetonate and 6 mg of nickel acetylacetonate were added. After sonication for 30 min, 50 mg of cetyltrimethylammonium bromide (CTAB) was added. The mixture was sealed and incubated in an oil bath at 180 °C to form a porous carbon-supported Pt-based alloy material / oleylamine mixed solution. After reacting for 50 min, the solution was allowed to cool naturally. The mixture was centrifuged at 10000 r / min to collect the precipitate, which was then repeatedly washed with ethanol for 20 min each time, for a total of 3 centrifugation washes. Finally, the precipitate was placed in a vacuum oven at 60 °C for 12 h, ground into powder, and set aside for later use.
[0055] 10 mg of the prepared porous carbon-supported Pt-based alloy material was weighed and dissolved in 30 mL of ethylene glycol. 50 μL of 6 mol / L hydrochloric acid was added, and the mixture was stirred for 15 min. Then, 3 mg of iridium acetate was added, and the mixture was sealed. The mixture was then placed in an oil bath at 150 °C for 30 min. After the reaction was completed, the mixture was allowed to cool naturally and centrifuged at 8000 r / min for 30 min. The mixture was washed three times with a 1:1 mixture of ethanol and deionized water. After centrifugation, the precipitate was placed in a vacuum oven at 60 °C and dried for 12 h to obtain the porous carbon-supported Ir-doped PtNi alloy catalyst.
[0056] Example 3
[0057] 15 mg of XC-72 carbon was dissolved in 30 ml of oleylamine and stirred continuously. Then, 8 mg of platinum acetylacetonate and 6 mg of copper acetylacetonate were added sequentially. After sonication for 30 min, 50 mg of cetyltrimethylammonium bromide (CTAB) was added. The mixture was sealed and subjected to an oil bath at 230 °C to form a porous carbon-supported Pt-based alloy material / oleylamine mixed solution. After reacting for 40 min, the solution was allowed to cool naturally. The mixture was centrifuged at 10000 r / min to collect the precipitate, which was then washed repeatedly with ethanol for 20 min each time, for a total of 3 centrifugation washes. Finally, the precipitate was placed in a vacuum oven at 60 °C for 12 h, ground into powder, and set aside for later use.
[0058] 15 mg of the prepared porous carbon-supported Pt-based alloy material was weighed and dissolved in 30 mL of ethylene glycol. 75 μL of 6 mol / L hydrochloric acid was added, and the mixture was stirred for 15 min. Then, 5 mg of iridium acetate was added, and the mixture was sealed. The mixture was then placed in an oil bath at 165 °C for 15 min. After the reaction was completed, the mixture was allowed to cool naturally and centrifuged at 8000 r / min for 30 min. The mixture was washed three times with a 1:1 mixture of ethanol and deionized water. After centrifugation, the precipitate was placed in a vacuum oven at 60 °C and dried for 12 h to obtain the porous carbon-supported Ir-doped PtCu alloy catalyst.
[0059] Example 4
[0060] 10 mg of XC-72 carbon was dissolved in 30 ml of oleylamine and stirred continuously. Then, 10 mg of platinum acetylacetone, 10 mg of copper acetylacetone, and 10 mg of nickel acetylacetone were added sequentially. After sonication for 30 min, 80 mg of cetyltrimethylammonium bromide (CTAB) was added. The mixture was sealed and placed in an oil bath at 200 °C to form a porous carbon-supported Pt-based alloy material / oleylamine mixed solution. After reacting for 50 min, the solution was allowed to cool naturally. The mixture was centrifuged at 10000 r / min to collect the precipitate, which was then washed repeatedly with ethanol. Each centrifugation was repeated 20 times for 20 min, and the washing was repeated 3 times. Finally, the precipitate was placed in a vacuum oven at 60 °C for 12 h, ground into powder, and set aside for later use.
[0061] 20 mg of the prepared porous carbon-supported Pt-based alloy material was weighed and dissolved in 30 mL of ethylene glycol. 100 μL of 6 mol / L hydrochloric acid was added, and the mixture was stirred for 15 min. Then, 7 mg of iridium acetate was added, and the mixture was sealed. The mixture was then placed in an oil bath at 150 °C for 30 min. After the reaction was completed, the mixture was allowed to cool naturally and centrifuged at 8000 r / min for 30 min. The mixture was washed three times with a 1:1 mixture of ethanol and deionized water. After centrifugation, the precipitate was placed in a vacuum oven at 60 °C and dried for 12 h to obtain the porous carbon-supported Ir-doped PtNiCu alloy catalyst.
[0062] Example 5
[0063] 15 mg of XC-72 carbon was dissolved in 30 ml of oleylamine and stirred continuously. Then, 6 mg of platinum acetylacetonate, 5 mg of copper acetylacetonate, and 5 mg of nickel acetylacetonate were added sequentially. After sonication for 30 min, 60 mg of cetyltrimethylammonium bromide (CTAB) was added, the mixture was sealed, and incubated in an oil bath at 180 °C to form a porous carbon-supported Pt-based alloy material / oleylamine mixed solution. After reacting for 60 min, the solution was allowed to cool naturally. The mixture was centrifuged at 10000 r / min to collect the precipitate, which was then washed repeatedly with ethanol for 20 min each time, for a total of 3 centrifugation washes. Finally, the precipitate was placed in a vacuum oven at 60 °C for 12 h, ground into powder, and set aside for later use.
[0064] 10 mg of the prepared porous carbon-supported Pt-based alloy material was weighed and dissolved in 30 mL of ethylene glycol. 50 μL of 6 mol / L hydrochloric acid was added, and the mixture was stirred for 15 min. Then, 3 mg of iridium acetate was added, and the mixture was sealed. The mixture was then placed in an oil bath at 165 °C for 15 min. After the reaction was completed, the mixture was allowed to cool naturally and centrifuged at 8000 r / min for 30 min. The mixture was washed three times with a 1:1 mixture of ethanol and deionized water. After centrifugation, the precipitate was placed in a vacuum oven at 60 °C and dried for 12 h to obtain the porous carbon-supported Ir-doped PtNiCu alloy catalyst.
[0065] Example 6
[0066] 20 mg of XC-72 carbon was dissolved in 30 ml of oleylamine and stirred continuously. Then, 15 mg of platinum acetylacetonate, 7 mg of copper acetylacetonate, and 7 mg of nickel acetylacetonate were added sequentially. After sonication for 30 min, 100 mg of cetyltrimethylammonium bromide (CTAB) was added. The mixture was sealed and incubated in an oil bath at 230 °C to form a porous carbon-supported Pt-based alloy material / oleylamine mixed solution. After reacting for 40 min, the solution was allowed to cool naturally. The mixture was centrifuged at 10000 r / min to collect the precipitate, which was then washed repeatedly with ethanol for 20 min each time, for a total of 3 centrifugation washes. Finally, the precipitate was placed in a vacuum oven at 60 °C for 12 h, ground into powder, and set aside for later use.
[0067] 20 mg of the prepared porous carbon-supported Pt-based alloy material was weighed and dissolved in 30 mL of ethylene glycol. 100 μL of 6 mol / L hydrochloric acid was added, and the mixture was stirred for 15 min. Then, 7 mg of iridium acetate was added, and the mixture was sealed. The mixture was then placed in an oil bath at 150 °C for 25 min. After the reaction was completed, the mixture was allowed to cool naturally and centrifuged at 8000 r / min for 30 min. The mixture was washed three times with a 1:1 mixture of ethanol and deionized water. After centrifugation, the precipitate was placed in a vacuum oven at 60 °C and dried for 12 h to obtain the porous carbon-supported Ir-doped PtNiCu alloy catalyst.
[0068] Example 7
[0069] 15 mg of XC-72 carbon was dissolved in 30 ml of oleylamine and stirred continuously. Then, 5 mg of platinum acetylacetonate and 5 mg of copper acetylacetonate were added sequentially. After sonication for 30 min, 20 mg of cetyltrimethylammonium bromide (CTAB) was added. The mixture was sealed and incubated in an oil bath at 210 °C to form a porous carbon-supported Pt-based alloy material / oleylamine mixed solution. After reacting for 30 min, the solution was allowed to cool naturally. The mixture was centrifuged at 10000 r / min to collect the precipitate, which was then washed repeatedly with ethanol for 20 min each time, for a total of 3 centrifugation washes. Finally, the precipitate was placed in a vacuum oven at 60 °C for 12 h, ground into powder, and set aside for later use.
[0070] 30 mg of the prepared porous carbon-supported Pt-based alloy material was weighed and dissolved in 30 mL of ethylene glycol. 75 μL of 6 mol / L hydrochloric acid was added, and the mixture was stirred for 15 min. Then, 3 mg of iridium acetate was added, and the mixture was sealed. The mixture was then placed in an oil bath at 120 °C for 10 min. After the reaction was completed, the mixture was allowed to cool naturally and centrifuged at 8000 r / min for 30 min. The mixture was washed three times with a 1:1 mixture of ethanol and deionized water. After centrifugation, the precipitate was placed in a vacuum oven at 60 °C and dried for 12 h to obtain the porous carbon-supported Ir-doped PtCu alloy catalyst.
[0071] Example 8
[0072] 15 mg of XC-72 carbon was dissolved in 30 ml of oleylamine and stirred continuously. Then, 8 mg of platinum acetylacetonate and 6 mg of copper acetylacetonate were added sequentially. After sonication for 30 min, 56 mg of cetyltrimethylammonium bromide (CTAB) was added. The mixture was sealed and incubated in an oil bath at 170 °C to form a porous carbon-supported Pt-based alloy material / oleylamine mixed solution. After reacting for 180 min, the solution was allowed to cool naturally. The mixture was centrifuged at 10000 r / min to collect the precipitate, which was then washed repeatedly with ethanol for 20 min each time, for a total of 3 centrifugation washes. Finally, the precipitate was placed in a vacuum oven at 60 °C for 12 h, ground into powder, and set aside for later use.
[0073] 15 mg of the prepared porous carbon-supported Pt-based alloy material was weighed and dissolved in 30 mL of ethylene glycol. 75 μL of 6 mol / L hydrochloric acid was added, and the mixture was stirred for 15 min. Then, 7.5 mg of iridium acetate was added, and the mixture was sealed. The mixture was then placed in an oil bath at 140 °C for 25 min. After the reaction was completed, the mixture was allowed to cool naturally and centrifuged at 8000 r / min for 30 min. The mixture was washed three times with a 1:1 mixture of ethanol and deionized water. After centrifugation, the precipitate was placed in a vacuum oven at 60 °C and dried for 12 h to obtain the porous carbon-supported Ir-doped PtCu alloy catalyst.
[0074] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a porous carbon-supported Ir-doped Pt-based alloy catalyst, characterized in that, Includes the following steps: Step 1: Porous carbon, platinum metal salt, and other metal salts are added to oleylamine to obtain a mixed system. After ultrasonic treatment of the mixed system, hexadecyltrimethylammonium bromide is added, and the mixture is treated in a sealed oil bath. After the oil bath treatment, the reaction product is centrifuged, washed, and dried to obtain a porous carbon-supported Pt-based alloy material. The other metal salts are metal salts corresponding to transition metals other than platinum metal salt and iridium metal salt. Step 2: Dissolve the porous carbon-supported Pt-based alloy material in ethylene glycol, add hydrochloric acid and stir, then add iridium acetate to form a reaction system; after the reaction system is treated in an oil bath, the reaction product is centrifuged, washed, and dried to obtain the porous carbon-supported Ir-doped Pt-based alloy catalyst.
2. The method for preparing a porous carbon-supported Ir-doped Pt-based alloy catalyst according to claim 1, characterized in that, In step 1, the mixing ratio of porous carbon to oleylamine is (10-20 mg): 30 mL; the mixing ratio of metal salt to oleylamine is (5-15 mg): 15 mL.
3. The method for preparing a porous carbon-supported Ir-doped Pt-based alloy catalyst according to claim 1, characterized in that, In step 1, the total amount of platinum salt and other metal salts added is ≤30mg.
4. The method for preparing a porous carbon-supported Ir-doped Pt-based alloy catalyst according to claim 1, characterized in that, In step 1, the amount of hexadecyltrimethylammonium bromide added is 2-4 times the total amount of metal salt added.
5. The method for preparing a porous carbon-supported Ir-doped Pt-based alloy catalyst according to claim 1, characterized in that, In step 1, the oil bath time is 30-180 minutes and the oil bath temperature is 170-230℃.
6. The method for preparing a porous carbon-supported Ir-doped Pt-based alloy catalyst according to claim 1, characterized in that, In step 2, the mixing ratio of porous carbon-supported Pt-based alloy material to ethylene glycol is (10-30 mg): 30 mL.
7. The method for preparing a porous carbon-supported Ir-doped Pt-based alloy catalyst according to claim 1, characterized in that, In step 2, the ratio of added hydrochloric acid to porous carbon-supported Pt-based alloy material is 5 μL: 1 mg.
8. The method for preparing a porous carbon-supported Ir-doped Pt-based alloy catalyst according to claim 1, characterized in that, In step 2, the amount of iridium acetate added is 0.1-0.5 times the amount of porous carbon-supported Pt-based alloy material added.
9. The method for preparing a porous carbon-supported Ir-doped Pt-based alloy catalyst according to claim 1, characterized in that, In step 2, the oil bath time is 10-30 minutes and the oil bath temperature is 120-165℃.
10. A porous carbon-supported Ir-doped Pt-based alloy catalyst prepared by the preparation method according to any one of claims 1-9, characterized in that, The porous carbon surface is coated with alloy nanoparticles, which are an alloy composed of Ir, Pt and metal M, where metal M is a transition metal other than Ir and Pt.
Citation Information
Patent Citations
Preparation method of nitrogen-doped porous carbon-supported metal monoatomic material
CN108579783A
Nitrogen-sulfur-doped porous carbon-modified carbon nanotube-supported Pt-Ni alloy catalyst and preparation method thereof
CN110813363A
